Developing a Real Time Method for the Arabic Heterogonous DBMS Transformation - Hadi, S. M.; Murtatha, S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A common problem facing many Application models is to extract and combine information from multiple, heterogeneous sources and to derive information of a new quality or abstraction level. New approaches for managing consistency, uncertainty or quality of Arabic data and enabling e-client analysis of distributed, heterogeneous sources are still required. This paper presents a new method by combining two algorithms (the partitioning and Grouping) that will be used to transform information in a real time heterogeneous Arabic database environment